Nefertiti - Moran,Michelle (Quercus, 2007)
Raised far from the Egyptian court with her sister, Mutnodjmet, the beautiful and ambitious Nefertiti becomes the wife of the radical new pharaoh, Amunhotep, encouraging his plans to overturn Egypt's state religion and making powerful enemies in the process, while her sister, recognizing her sister's dangerous position, does what she can to protect her family.